Comparing Care of the Primary and Secondary Hemochromatosis Patients. Issue 2 (March 2020) - Becker, Susan
Abstract : Hemochromatosis is an imbalance of excessive serum iron and is a life-threatening condition if left untreated. Due to different causes, primary and secondary hemochromatosis have different patient care considerations for the infusion nurse. Understanding the pathophysiology and how the body absorbs iron is imperative for providing the highest quality care. Since primary (hereditary) hemochromatosis originates from a gene mutation, and secondary (acquired) from excessive intake, the treatment and education must be adjusted accordingly to deliver successful outcomes for both diagnoses.